MINIMALLY INVASIVE GLAUCOMA SURGICAL TECHNIQUES FOR OPEN-ANGLE GLAUCOMA : A SYSTEMATIC REVIEW - Emir Hassan, Fauzan; Azhari, Ririn; Adenita, Qoshrina; Syarfina, Afdila; Ananda, Astrid (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Glaucoma affects more than 75 million people worldwide. Intraocular pressure (IOP) lowering surgery is an important treatment for this disease. Interest in reducing surgical morbidity has led to the introduction of minimally invasive glaucoma surgeries (MIGS). Understanding the comparative effectiveness and safety of MIGS is necessary for clinicians and patients. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 318 articles, whereas the results of our search on SagePub brought up 34 articles. The results of the search conducted for the last year of 2013 yielded a total 13 articles for PubMed and 12 articles for SagePub. In the end, we compiled a total of 5 papers, 4 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion: Although MIGS seem efficient in the reduction of the IOP and glaucoma medication and show good safety profile, this evidence is mainly derived from non-comparative studies and further, good quality RCTs are warranted.